Comparison of microcomputed tomography, cone beam tomography, stereomicroscopy, and scanning electron microscopy techniques for detection of microcracks on root dentin and effect of different apical sizes on microcrack formation - Capar, Ismail D.; Gok, Tuba; Uysal, Banu; Keles, Ali (Wiley, 2019)
The aim of the study was to compare different imaging methods in the diagnosis of microcracks on root dentin and to evaluate the frequency of dentinal microcracks observed after root canal preparation using the ProTaper Universal (PTU) system of different sizes. A total of 30 mandibular molars' mesial roots were scanned with microcomputed tomography (micro-CT) and cone beam computed tomography (CBCT) imaging methods before instrumentation. Root canal instrumentation was performed up to PTU F2 and F4 files. After instrumentation stages, the roots were scanned again with micro-CT and then with CBCT in same parameters. All roots were sectioned horizontally at 2, 4, 6, 8, and 10 mm from the apices of the specimens. The sections were imaged under a stereomicroscope. Finally, imaging of the sections was done by scanning electron microscopy (SEM). Statistical data analysis of instrumentation steps was performed using Friedman and Wilcoxon tests, and the data of imaging methods were analyzed using Kruskal-Wallis and Mann-Whitney U tests (p = .05). Instrumentation with the PTU system up to F2 and F4 files significantly increased the number of microcracks compared with preoperative samples according to micro-CT imaging (p < .05). For detecting microcracks on the root dentin, there were no statistically significant differences between micro-CT (43.9%) and stereomicroscopy (45.8%) (p < .05). SEM showed significantly higher percentage of microcracks (88.3%) (p > .05). No microcrack was observed using the CBCT method. There were no statistically differences between micro-CT and stereomicroscopy. SEM showed more dentinal microcracks while no microcrack was observed with CBCT.
Keywords: cone beam computed tomography; dentinal microcrack; micro-computed tomography; scanning electron microscopy; stereomicroscopy